Magnetic and Microwave Absorption Properties of Magnetite (Fe3O4)@ Conducting Polymer (PANI, PPY, PT) Composites - Unver, Ibrahim Saim; Durmus, ZEHRA (My University, 2017)
Magnetite nanoparticles (Fe3O4 NPs) were synthesized via reflux co-precipitation method and coated with various polymeric media of polypyrrole (PPY), polyaniline (PANI), and polythiophene (PT) in the same experiment conditions. The increasing crystallinity and the absence of another phase were investigated from X-ray diffraction experiments. Fe3O4 NPs have spherical shapes and after polymer coating their mean size were found as 11.76, 11.51, and 9.98 nm for Fe3O4@ PPY, Fe3O4@ PANI, and Fe3O4@ PT, respectively. The superparamagnetic nature of composites was observed at room temperature. The electromagnetic (EM) wave reflection loss of samples was analyzed comparatively. It was found that the type of the polymers coated on the magnetite nanoparticles in the same procedure gives slight change in reflection loss of EM waves.